A diverse and partially cellulolytic fungal community contributes to the diet of three species of the aquatic insect phylloicus (Trichoptera: Calamoceratidae) in amazonian streams - Morais, Paula B. de; Pes, A. M.; Santos, Taides T.Dos (Anais da Academia Brasileira de Ciencias, 2021)
Investigations on the fungal community associated with the digestive tract (DT) of insects have provided insights into the diversity of associated microorganisms and their potential roles in the interaction with their hosts. However, most studies have focused on terrestrial insects, with few studies focusing on aquatic insects in Neotropical regions. We studied fungal taxa associated with the DT of larval stages of the aquatic shredders Phylloicus amazonas, P. elektoros and P. fenestratus in the Brazilian Amazon Forest. Filamentous fungi were isolated, purified and screened for cellulolytic activity. A total of 33 fungal taxa was identified through the combination of classical and molecular taxonomy. The genus Penicillium was the most frequent in DT of Phylloicus spp. (18.75%). The occurrence of fungal taxa among hosts was quite variable, with more than half of the associated fungi being exclusive of each host species. A significant portion of the fungal community associated with each host presented cellulolytic activity (± 50%). It was concluded that the fungal community associated with Phylloicus spp. larvae consist mainly of fungal taxa from food items, which come from riparian vegetation (whose plant species are variable) or are indigenous of the aquatic ecosystems, which is the habitat of these larvae. © 2021, Academia Brasileira de Ciencias. All rights reserved.
Keywords: Cellulolytic fungi; Digestive tract